Race and Death Sentencing for Oklahoma Homicides Committed Between 1990 and 2012 - Pierce, Glenn L. (2017)
This Article examines 4,668 Oklahoma homicide cases with an identified suspect that occurred during a twenty-three year period between January 1, 1990, and December 31, 2012. Among these, we identified 153 cases that ended with a death sentence. Overall we found that while the defendant’s race did not correlate with a death sentence, there was a strong correlation with the race of the victim, with cases with white victims significantly more likely to end with a death sentence than cases with non-white victims. Homicides with female victims were also more likely to result in a death sentence than other cases. We then examined whether the homicide included multiple victims and/or additional felony circumstances, and coded each case to indicate whether it included zero, one, or two of these “additional legally relevant factors.” Using logistic regression analysis, where the effects of each predictor variable can be isolated, the data indicate that 1) having a white female victim, 2) having a white male victim, 3) having a female victim from a minority race or ethnicity, 4) having one additional legally relevant factor, and 5) having two additional legally relevant factors present are statistically significant predictors of a death sentence. Overall, the data show that the odds of a death sentence for those with white female victims are 9.59 times higher than in cases with minority male victims. The odds of a death sentence for those with white male victims are 3.22 times higher than the odds of a death sentence with minority male victims. Finally, the odds of a death sentence for those with minority female victims are 8.68 times higher than the odds of a death sentence with minority male victims. All these race/gender effects are net of our two control variables (multiple murder victims and the presence of additional felony circumstances)